Change in Land Value in Kathmandu City (1954-1978) - Manandhar, Mangal Siddhi; Ranjitkar, Nanda Gopal (Himalayan Review, 2011)
Not available. Key words: Value of land; Numerous value; Kathmandu The Himalayan Review Vol. 13, 1981 Page: 72-83 Uploaded Date: April 8, 2011